2007
DOI: 10.1007/s11745-007-3086-9
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of c9,t11–18:2 or t10,c12–18:2 Enriched Dietary Supplements Does Not Influence Milk Macronutrients in Healthy, Lactating Women

Abstract: Substantial research suggests that the t10,c12-18:2, but not the c9,t11-18:2, isomer of conjugated linoleic acid (CLA) reduces milk fat synthesis in lactating bovine and rodent species. Because fat is the major energy-yielding component in human milk, we were interested in whether this is true for women as well. Thus, the effects of c9,t11-18:2 and t10,c12-18:2 on milk fat were examined in breast-feeding women (n = 12) in a double-blind, placebo-controlled, crossover study with latin-square design. The study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The treatment effects observed on milk fatty acid profiles add more evidence that the participants adhered to the guidelines of the study. In particular, the elevation of milk c9,t11-CLA content during the full-fat dairy intervention largely verifies subjects' compliance [3,29]. The differential amounts of c9,t11-CLA in the milk lipids also suggest that the dietary intervention was successful in changing the exposure of the lactating mammary epithelial cell to this potentially biologically active fatty acid.…”
Section: Discussionmentioning
confidence: 84%
“…The treatment effects observed on milk fatty acid profiles add more evidence that the participants adhered to the guidelines of the study. In particular, the elevation of milk c9,t11-CLA content during the full-fat dairy intervention largely verifies subjects' compliance [3,29]. The differential amounts of c9,t11-CLA in the milk lipids also suggest that the dietary intervention was successful in changing the exposure of the lactating mammary epithelial cell to this potentially biologically active fatty acid.…”
Section: Discussionmentioning
confidence: 84%
“…Two human studies focused on CLA and milk fat and found no changes in milk fat or protein (Hasin et al, 2007;Mosley et al, 2002). However, since the studies only used a relatively short period (5 days), it is still not clear if longer CLA supplementation would reduce milk fat content significantly enough to affect infant nutrition.…”
Section: Safety Concern For Humansmentioning
confidence: 99%
“…14 Analyzing breast milk from women receiving supplementation with CLA was observed in the milk the presence of CLA isomers but there were no modifications in the macronutrients composition. 15,16 Preliminary studies showed that dietary CLA offered to pregnancy and/or lactating rats are able to crossing the blood-brain barrier of the offspring and stay until a postnatal period. 17 However, it has been observed that an outcome of drinking goat milk (which CLA is included) versus cow's milk increased weight gain, length, and skeletal mineralization in rats.…”
Section: Introductionmentioning
confidence: 99%